Prawa człowieka. Zagadnienia podstawowe - Wojciechowski, Bartosz (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The paper refers to the genesis of legally binding human rights and discusses their claim to universal validity against the backdrop of the Western culture and philosophical debates (Kant, Bentham). It also presents the most current charges raised against human rights’ universal commitment, presented by such prominent thinkers as Amartya Sen. Invoking the concept of human dignity, author of the article argues in favour of universal validity of human rights.